PEMBELAJARAN DARING DI STKIP PARIS BARANTAI KOTABARU - Rudy Suryana; Andi Muhammad Yahya (STKIP Paris Barantai, 2021)
This research to get an idea of ​​how online learning in the PBSI prodi STKIP Paris Barantai as the Minister of Education and Culture of the RI said that learning in tertiary institutions in all zones is still required to be carried out online This research is a descriptive study with the aim of getting an overview of the implementation of online learning in the PBSI Study Program. The data were obtained from students in semester I and III. research was conducted by surveying students with google classroom in the first semester 46 students and 18 students in the third semester. There were 64 subjects who responded to the distributed survey. PBSI Study Program student research subjects, data collection is done through google classroom questionnaires. The conclusion of the student research has had facilities for 49 respondents who use laptop 3 people (6.12%) and smartphone users 46 (93.88%) people. Preferred WA 45.24%, Google Meeting 30.95%, Zoom 14.29% and Classroom 9.52%. Online learning is preferred because flexible in place and time, convenience and increased independence. Some students find it difficult to understand the material because of limited interactions. 87.76% of students did not receive Free Internet Quota Assistance and 12.24% did.